Praktik Simpan Pinjam Di Bank Sampah Kota Kediri Dalam Perspektif Hukum Ekonomi Islam - M Uzeir Mustaqfirin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
The purpose of this study is to find out the practice of saving and borrowing conducted by The Melati Garbage Bank given Islamic economic law. By using qualitative approaches and techniques of member chek and triangulation this research resulted in the conclusion that saves and borrows at Bank Sampah Melati and Bank Sampah Sri Wilis using an interesting system. In Islam, interest is equated with riba which is illegal, but the practice of saving and borrowing in the Melati Garbage Bank and Sri Wilis Garbage Bank has shown improvement. Interest on deposits aims to generate the excitement of members to save. While in the loan activities are helpful to members who need financial assistance and the interest rate is relatively low